Cloning, characterization and expression of sesquiterpene synthase 1 and delta guaiene synthase 1 genes associated with 'Gaharu" formation in aquilaria malaccensis Lam - Anor Basah, Azzarina (2015)
'Gaharu' is a valuable fragrant resin produced by several Aquilaria spp., many of which are considered threatened. The product is highly recognized for its vast medicinal values as a digestive, sedative and antiemetic drug and also popular as perfumes and incenses in the Middle East, South Asia, Japan and China. Additionally, 'gaharu' sculpturing for interior decoration is another important of its value which generates an income in Asia. Phytochemical studies revealed that sesquiterpenes are one of the main components in gaharu. Therefore, in this study, two genes, sesquiterpene synthase 1 and o-guaiene synthase 1 in the terpenoid biosynthesis pathway have been successfully cloned from A. malaccensis. These encoding genes were successfully isolated by rapid amplification of cDNA ends. They were designated as SesTPSI and GuaiSI, respectively. In the course of obtaining high quality RNA for gene cloning experiments, callus was successfully induced from leaf tissues of in vitro A. malaccensis on Murashige & Skoog medium supplemented with 2.2 11M6-Benzylaminopurine (BAP) and 1.1 11Mnaphthaleneacetic acid (NAA). Cell line A2 and A4 developed into healthy calli with cremish yellow color and the increased in diameter measurement. SesTPSI and GuaiSI were cloned from callus RNA, using specific primers derived from transcriptomic data, in a reverse transcription-PCR reaction. The results, the full-length cDNA sequence of SesTPSI was 1632 bp encoding for 544 amino acids, while GuaiSI was 1644 bp encoding for 547 amino acids. Sequence alignment analysis showed that SesTPSI shared between 99% to 100% identity with sesquiterpene synthase from Aquilaria sinensis while GuaiSI shared between 95% to 99% identity with o-guaiene synthases from Aquilaria crassna and A. sinensis. The genes were functionally characterized in a time-course wounding experiment using 3-year-old living trees. Two types of wood samples were collected: 1) from wounded area (S 1) and, 2) from 5 cm below the wounded area (S2). SesTPSl was highly expressed after 6 hours post wounding for both SI and S2, at a level 3-to 6-folds higher than that of control (0 h). The expression of SesTPSl was downregulated between 8 h to 24 h after which it climbed to between I-to 2-fold at 48 h. The pattern of expression of GuaiSl was not very different when compared to SesTPSl. GuaiSl was drastically induced after just 2 h of wounding to 2.8-folds. The expression levels fell back to lower levels (I-fold of control) but increased to 2-folds at 24 h. The expression patterns of SesTPSl and GuaiSl prevealed that they both responded similarly to wounding. In conclusion, fulllength SesTPSl and GuaiSl genes were successfully cloned from A. malaccensis. This is the first report on sesquiterpene genes from this species. It can be deduced that wounding triggers genes in the sesquiterpene synthesis pathway and that might lead to 'gaharu' formation.